2005
DOI: 10.1097/01.csmr.0000306211.02681.d3
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxy-β-Methylbutyrate and Its Use in Athletics

Abstract: Nutritional supplements are widely used by patients and athletes around the world for many different reasons. Many companies are thriving on this billion-dollar industry with little proof that these substances do what they are reported or suggested to do. Beta-hydroxy-beta-methylbutyrate (HMB) is a relatively new supplement on the ergogenic landscape. Studies of HMB supplementation have shown minimal gains in strength and lean body mass in specific populations, mainly untrained athletes and patients with wasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…It is believed to attenuate protein breakdown after workouts and has recently gained greater attention among athletes [88]. A 2013 NCAA survey study reported a 0.2 % rate of use among all student athletes [13].…”
Section: Beta-hydroxy-beta-methylbutyratementioning
confidence: 99%
“…It is believed to attenuate protein breakdown after workouts and has recently gained greater attention among athletes [88]. A 2013 NCAA survey study reported a 0.2 % rate of use among all student athletes [13].…”
Section: Beta-hydroxy-beta-methylbutyratementioning
confidence: 99%
“…Several studies supported the efficacy of HMB supplementation to improve sport performance by enhancing recovery [50,51] , lean body mass [50,52] , strength [53] , power [54] , and aerobic performance [55] in athletes. However, other studies documented a more evident improvement in untrained subjects with respect to athletes [56][57][58][59] . For example, Palisin and Stacy [59] reported that HMB supplementation determined gains in strength and lean body mass in patients with wasting syndromes.…”
Section: Role Of β-Hydroxy-β-methylbutyrate On Sport Performancementioning
confidence: 88%
“…However, other studies documented a more evident improvement in untrained subjects with respect to athletes [56][57][58][59] . For example, Palisin and Stacy [59] reported that HMB supplementation determined gains in strength and lean body mass in patients with wasting syndromes. Rowlands and Thomson [58] analyzed the effectiveness of HMB supplementation (range 1.5-6.0 g/day) on strength, body composition, and muscle damage in trained and untrained young men.…”
Section: Role Of β-Hydroxy-β-methylbutyrate On Sport Performancementioning
confidence: 88%
“…HMB functions are well known. It is an anti-catabolic agent associated with protein synthesis and attenuation of protein degradation [3,4], which makes it suitable for increasing strength and muscle mass in sport nutrition [5][6][7][8][9], as well as for clinical situations of increased protein degradation (cachexia), decreased rate of muscle protein synthesis (inactivity), or alteration of both (sarcopenia) [10][11][12]. In addition, it is a substrate for the synthesis of cholesterol needed to form and stabilize sarcolemmas in muscle [5], it has immune modulator properties [13,14], it downregulates apoptosis during immobilization and recovery [15] and also it produces improvement in oxidative metabolism [16].…”
Section: Introductionmentioning
confidence: 99%